Synergistic effect of mulch and nitrogen management on growth and essential oil yield of Salvia sclarea L. - Diksha Dhiman; Sakshi Vishvamitera; Sidharth Baghla; Sanatsujat Singh; Dinesh Kumar; Ashok Kumar; Ramesh Chauhan (Scientific Reports)
Abstract Balanced plant nutrition and optimal micro-climate are critical for achieving higher production sustainably. Substituting mineral fertilizers with organic amendments under water-conserving strategies like mulch can enhance the quality and yield and improve soil health. Therefore, a two-year study was conducted to examine the synergistic effects of mulch and reducing inorganic fertilizers and partially substituting organic amendments on essential oil (EO) yield and its composition, and soil properties in Salvia sclarea, an industrially important crop. Two mulching practices (M1: without mulch; M2: with mulch) and five nitrogen (N) management practices [N1: control; N2: 100% recommended dose of N i.e.,120 kg/ha; N3: 25% N through chemical fertilizer (CF) + 75% N through farm yard manure (FYM); N4: 50% N through CF + 50% N through FYM, N5: 75% N through CF + 25% N through FYM] were taken as experimental treatments, with a total of ten treatment combinations in a split-plot design during 2021-22 and 2022-23. The results showed that applying mulch increased the plant height, leaf area index (LAI), and EO yield. Among N management practices, N2 outperformed for all the morpho-physiological and yield parameters studied except stem diameter and produced at par outcomes with N5 in case of flower spike per plant, LAI, chlorophyll a and b, flower spike yield, EO content and yield. Optimum soil temperature and moisture under mulching modulate the nutrient concentration; similarly, N being necessary for photosynthesis, translocation of nutrients, enzymatic activity, and vegetative and reproductive growth, synergistically enhanced the EO yield and altered the composition. The heat map displayed an inconsistent pattern of the treatment combination’s impact on EO components. In soil properties, treatment N5 recorded highest value of available N at 0–0.15 m soil depth; however, at 0.15–0.30 m, N2 registered a higher value and produced at par results with N5. In case of potassium and soil organic carbon, T3 recorded higher value, followed by T4 and T5 at 0–0.15 m. Considering the soil health and without compromising the EO yield much, the present study suggested replacing 25% of recommended chemical N with organic manures under mulch for sustainable and economical production of S. sclarea.